2022
DOI: 10.1002/nbm.4757
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cellular responses in three‐dimensional cell cultures through chemical exchange saturation transfer and 1H MRS

Abstract: Metabolic responses to physiological changes have been detected using chemical exchange saturation transfer (CEST) imaging in clinical settings. Similarly to other MRI techniques, the CEST technique was based originally on phantoms from buffer solutions and was then further developed through animal experiments. However, CEST imaging can capture certain dynamics of metabolism that solution phantoms cannot model. Cell culture phantoms can fill the gap between buffer phantoms and animal models. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…33 Also, to bridge the gap between solution phantoms and in vivo studies, Wu et al showed that 2D and 3D cell culture phantoms can play an important role in interpreting many CEST signals. 34 Here, they showed that CEST signals in cell culture phantoms were sensitive to incubation time over several days. 34 In conclusion, it is fair to say that the submission of 18 review articles and 9 research manuscripts reflects that the CEST MRI field is active and continuing to grow.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…33 Also, to bridge the gap between solution phantoms and in vivo studies, Wu et al showed that 2D and 3D cell culture phantoms can play an important role in interpreting many CEST signals. 34 Here, they showed that CEST signals in cell culture phantoms were sensitive to incubation time over several days. 34 In conclusion, it is fair to say that the submission of 18 review articles and 9 research manuscripts reflects that the CEST MRI field is active and continuing to grow.…”
mentioning
confidence: 92%
“…34 Here, they showed that CEST signals in cell culture phantoms were sensitive to incubation time over several days. 34 In conclusion, it is fair to say that the submission of 18 review articles and 9 research manuscripts reflects that the CEST MRI field is active and continuing to grow. We hope that this special issue will increase the interest in the different saturation transfer methods even further, and following the example of APTw MRI lead to important clinical applications.…”
mentioning
confidence: 92%
See 2 more Smart Citations